CLINICAL FEATURES IN NEPHROTIC SYNDROME PATIENTS: A CASE REPORT - Maylisca Theresia Mulya Diprasta, Made; Diarnasa Zihara Safira, Lavenda; Larassanti, Levina; Amin, M. Shadiqul; Pratama Adiwinoto, Ronald (Riviera Publishing, 2024)
Nephrotic Syndrome is a glomerular disease characterized by edema, massive proteinuria >3.5 grams/day, hypoalbuminemia <3.5 grams/day, hypercholesterolemia, and lipiduria. Nephrotic syndrome has a variety of metabolic effects that impact the individual. Some episodes of nephrotic syndrome are self-limited, and some respond to specific therapy, while others are chronic. A 49 year old female patient complained of frequent sweats at night and chills in the morning. Then, the patient complained that his legs had been swollen since he left the hospital until now. Apart from that, edema also occurs in the lower extremities. The management given is general management such as rest, low cholesterol, low salt, fluid restriction <1500ml, and a protein diet. Treatment of edema with diuretics, treatment of proteinuria, treatment of hypertension and history of stroke, as well as causal treatment according to the etiology of nephrotic syndrome. The patient has undergone management planning and treatment therapy for nephrotic syndrome.